From Feeds To Beaches: Social Media Driving Coastal Tourism - Wahyu Setiawan; Nur Azizah (Politeknik Pariwisata Makassar, 2024)
This study aims to analyze the impact of social media on Generation Z and Millennial tourists' motivation to visit marine tourism destinations in Gunungkidul, Yogyakarta. As digital natives, these generations are particularly influenced by social media in their travel decisions, making them a crucial demographic for understanding the evolving landscape of tourism marketing. The research employs a quantitative approach with questionnaire survey. A total of 300 respondents (150 Gen Z and 150 Millennials) who have visited or plan to visit marine tourism destinations in Gunungkidul were surveyed online. Data analysis utilized SMART PLS to examine the relationships between social media engagement, destination image, and travel motivation. The findings reveal a strong positive correlation between social media engagement and the motivation to visit Gunungkidul's marine destinations among both generations. Instagram and TikTok emerged as the most influential platforms, with user-generated content and influencer collaborations playing pivotal roles in shaping destination perceptions. Interestingly, Gen Z showed a higher susceptibility to peer recommendations and viral challenges, while Millennials were more influenced by informative content and authentic travel experiences shared on social media. The study contributes to the theoretical understanding of social media's role in shaping young tourists' motivations in the context of marine tourism. It also provides practical implications for destination marketers and tourism stakeholders in Gunungkidul, offering strategies to effectively leverage social media platforms to attract Gen Z and Millennial visitors